Structural and palaeoclimatic implications of submarine gullies on the Gulf of Cadiz upper slope from high and very high resolution seismic stratigraphic studies - García, Marga; Llave Barranco, Estefanía; Hernández-Molina, Francisco J.; Mena, Anxo; Ercilla, Gemma; Casas, David; Fernández Salas, Luis Miguel (2017)
Deep-Water Circulation Conference: Multidisciplinary Perspective (3º. 2017. Wuhan, China) The Gulf of Cadiz upper slope records the interplay between mass movement processes, mostly channelized flows along downslope-trending submarine gullies, and the action of bottom currents, in an area where paleoclimatic changes may have led to important variations of the oceanographic conditions, especially between glacial and interglacial periods. This work investigates the evolution of downslope-trending gullies in the upper slope of the Gulf of Cadiz, based on the analysis of high and very high resolution seismic record (Parasound and airgun profiles) and their correlation with regional stratigraphic interpretations. The gullies can be identified in the present-day seafloor as parallel downslope-trending features (10-15 km long, 1-1.5 km wide, up to 50 m deep). Their heads lie below the continental shelf-break and they terminate abruptly at the base of the upper slope, where they meet the Cadiz Contourite Channel along the middle slope. A seismic stratigraphic correlation allows identifying gully-like depressions in the seismic record from the Middle Pleistocene. Their high spatial and temporal variability can be related to the activity of the deep structures (particularly diapiric ridges) and in some cases to fluid escape processes that affect the region. The evolution of the gullies since the Mid Pleistocene can be established in order to infer the effect of climatic and structural changes that affect the circulation patters in the Gulf of Cadiz (i.e., changes in the trend, depth and velocity of the Mediterranean Outflow Water and other water masses such as the Eastern North Atlantic Central Water and the Superficial Atlantic Water but also changes affecting the interfases between water masses) from the variations in the sedimentation processes of the upper slope Instituto Geológico y Minero de España, España Consejo Superior de Investigaciones Científicas, España Peer reviewed